Exercise prescription to improve inhibitory control in children and adolescents with ADHD: a network meta-analysis - Zhao, Ke; Li, Yongxiao; Wang, Penglong; Zhang, Ping (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the effects of different combinations of exercise prescription variables (type, duration, frequency, period, intensity) on inhibitory control in children and adolescents with ADHD, and to provide a basis for the development of exercise prescriptions for intervening inhibitory control in children and adolescents with ADHD.MethodsData sources were searched up to February 1, 2025, including Scopus, PubMed, Web of Science, Embase, and Cochrane. The Cochrane Risk of Bias Assessment Tool was utilized for methodological quality assessment. Stata 17.0 software was used for net meta-analysis to compare the interventions with each other, using standardized mean difference (SMD) and 95% CI as the effect indicators. The effect differences between the interventions were compared using standardized mean difference (SMD) and 95% CI as effect indicators, and the effects of exercise prescription variables were ranked using Surface Under the Cumulative Ranking Area (SUCRA).ResultsTwenty papers with 1450 participants aged 7–18 years were finally included. Net Meta-analysis showed that the intervention duration of 70 minutes (SMD=2.15, 95% CI (1.02,3.28)) was significantly better than the control group. The intervention effect was significantly better for 2 times per week (SMD=1.27, 95% CI: (0.65,1.90)) than for the control group, and the intervention effect for at least 20 weeks (SMD=1.37, 95% CI (0.32,2.41)) was significantly better than the intervention effect for 12 weeks. moderate to high intensity (SMD = -0.14, 95% CI (-0.68, -0.40)) was significantly lower than moderate intensity (all P values < 0.05). The ranking of the SUCRA results showed that the intervention effect of Taekwondo (SUCRA=87.1), 70 minutes/repetition (SUCRA=99.0), twice per week (SUCRA=97.8), and continued for at least 20 weeks (SUCRA=92.5) and moderate intervention intensity (SUCRA=98.9) may have the best effect on inhibitory control effects in children and adolescents with ADHD.ConclusionThis study found that for the improvement of inhibitory control in children and adolescents with ADHD, a moderate-intensity taekwondo exercise intervention model of 70 minutes twice a week for at least 20 weeks can achieve more satisfactory results, which provides a program choice with reference value for relevant clinical intervention practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251019338.